Transitivity in Adila Hassim Speech at the ICJ (International Court Justice): South Africa’s Case Against Israel - Fauziah; Simatupang, Ervina (Universitas Veteran Bangun Nusantara, 2024)
This study aims to observe and analyse the transitivity process appears in the speech, investigate the construction of ideational meaning from the speech: how the transitivity patterns reflect the messages conveyed by Adila Hassim in her speech at the ICJ (International Court Justice). The transitivity analysis of Adila Hassim's speech at the ICJ reveals a strategic use of different processes to construct ideational meaning. The material process is most prominent (13 or 43.33%), emphasizing actions and events. The relational process follows (10 or 33.33%), highlighting relationships and attributes. Verbal and mental processes each account for 6.66% (2 verbal and 2 mental process) reflecting the importance of communication and cognition. The existential process, (3 or 10%), put the speech in reality. The absence of behavioral processes indicates no focus on behaviors. Adila Hassim's speech effectively combines these processes to present a strong and powerful argument for South Africa’s case against Israel at the ICJ.